Rigid and Non-Rigid Forms - Ford, Lewis S. (Process studies, 2007)
Eternal objects are rigid, being invariant in all their appearances in the world, as well as in the becoming of actual entities. This rigidity within concrescence generates several difficulties, and so I propose that forms within concrescence, both divine and finite, be modifiable. Thus there can be a formation of form. Each eternal object then becomes completely determinate in a finite actualization, and remains so determinate throughout its worldly career.